Pengenalan dan Implementasi Teknologi UAV untuk Pembelajaran di Madrasah Aliyah - Yuliza, Elfi; Ekawita, Riska; Intara, Yazid Ismi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: Therefore, the aim of this activity is to increase the knowledge and skills of the participants in using drone technology.   Methodology/approach: To accomplish these goals, the activity unfolds in four main stages: preparation, equipment presentation, demonstration, and hands-on operation. In this program, the civitas of Bengkulu University provided material related to drone types, configurations, and applications, along with drone data processing techniques. Results/findings: The program included practical demonstrations and training sessions on drone operation. During this program, participants, consisting of second-year students and accompanying teachers, had the opportunity to participate in hands-on drone piloting exercises. Furthermore, questionnaires were distributed to assess participants' comprehension before and after the sessions. Throughout the program, the audience showed great enthusiasm about being able to operate and apply this drone. Conclusion: The drone-related community service program was intended to enhance students’ knowledge and skills regarding emerging technologies. Based on the questionnaire results, students’ knowledge increased by more than 50%. Limitations: This activity only focused on participants of class II students of Madrasah Aliyah Mambaul ‘Ulum (MAMU) and accompanying teachers. Additionally, the training emphasizes drone operation and data processing techniques for various applications. Contribution: This activity enhances participants' hard skills in drone operation and data application, as well as their soft skills, enabling them to utilize the data in various fields such as education, tourism, and more.